Slower molecular response to treatment predicts poor outcome in patients with TEL/AML1 positive acute lymphoblastic leukemia: prospective real-time quantitative reverse transcriptase-polymerase chain reaction study - Madzo, Jozef; Zuna, Jan; Muzíková, Katerina; Kalinová, Markéta; Krejcí, Ondrej; Hrusák, Ondrej; Otová, Berta; Starý, Jan; Trka, Jan (Cancer, 2003)
BACKGROUND: The translocation t(12;21)(p13;q22), which produces the TEL/AML1 fusion gene, is the most frequent chromosomal abnormality in patients with childhood acute lymphoblastic leukemia (ALL) and generally is associated with a favorable prognosis. Furthermore, real-time quantitative-polymerase chain reaction (RQ-PCR)-based detection of TEL/AML1 represents an accurate technique for the reproducible assessment of minimal residual disease (MRD). METHODS: The authors employed RQ-reverse transcriptase-PCR (RQ-RT-PCR) technology to analyze MRD levels in 57 newly diagnosed patients with TEL/AML1 positive ALL in a prospective study. RESULTS: On Day + 33, a particularly important time point in terms of outcome prediction based on MRD monitoring, 75% of patients reached negativity, 13% of patients were positive at very low levels (< 10(-4); i.e., 1 or more leukemic cell per 10(4) normal cells), and another 13% of patients were positive at the level of 10(-2) to 10(-4) cells. No patient showed MRD levels > or = 10(-2) cells at this time. The data demonstrate that patients with TEL/AML1 positive ALL had a better response to induction chemotherapy on Day + 33 compared with a group of unselected patients with ALL (P = 0.0001). However, four patients with TEL/AML1 positive ALL developed relapse disease. Remarkably, these children were positive for MRD on Day + 33 at a level between 10(-2) cells and 10(-4) (n = 3 patients) and at < 10(-4) (n = 1 patient). Kaplan-Meier analysis of disease free survival showed the statistical significance of this distribution (MRD positive vs. MRD negative; log-rank P = 0.0016). CONCLUSIONS: The authors conclude that, although the TEL/AML1 positive leukemias generally are associated with a favorable outcome, MRD positivity assessed by RQ-RT-PCR analysis at the end of induction therapy represents a significantly negative prognostic feature.
Keywords: Neoplasm, Residual; akutní lymfatická leukemie; Female; Infant; dítě; předškolní dítě; novorozenec; Chromosomes, Human, Pair 12; výsledek terapie; ženské pohlaví; přežití bez známek nemoci; fúzní onkogenní proteiny; Adolescent; RNA nádorová; lidé; Translocation, Genetic; Infant, Newborn; lidské chromozomy, pár 21; Antineoplastic Agents; protinádorové látky; reziduální nádor; DNA primery; messenger RNA; polymerázová řetězová reakce s reverzní transkripcí; následné studie; Oncogene Proteins, Fusion; Treatment Outcome; RNA, Messenger; prospektivní studie; Follow-Up Studies; Male; Reverse Transcriptase Polymerase Chain Reaction; kojenec; Prospective Studies; lidské chromozomy, pár 12; Child, Preschool; protein PEBP2A2; Chromosomes, Human, Pair 21; RNA, Neoplasm; Disease-Free Survival; Precursor Cell Lymphoblastic Leukemia-Lymphoma; DNA Primers; Child; mužské pohlaví; translokace genetická; mladiství; Core Binding Factor Alpha 2 Subunit; Humans